Variation of BMP3 contributes to dog breed skull diversity. - Jeffrey J Schoenebeck; Sarah A Hutchinson; Alexandra Byers; Holly C Beale; Blake Carrington; Daniel L Faden; Maud Rimbault; Brennan Decker; Jeffrey M Kidd; Raman Sood; Adam R Boyko; John W Fondon; et al. (PLoS Genetics)
Since the beginnings of domestication, the craniofacial architecture of the domestic dog has morphed and radiated to human whims. By beginning to define the genetic underpinnings of breed skull shapes, we can elucidate mechanisms of morphological diversification while presenting a framework for understanding human cephalic disorders. Using intrabreed association mapping with museum specimen measurements, we show that skull shape is regulated by at least five quantitative trait loci (QTLs). Our detailed analysis using whole-genome sequencing uncovers a missense mutation in BMP3. Validation studies in zebrafish show that Bmp3 function in cranial development is ancient. Our study reveals the causal variant for a canine QTL contributing to a major morphologic trait.